German registry for acute aortic dissection type A (GERAADA): lessons learned from the registry - Weigang, Ernst; Conzelmann, Lars Oliver; Kallenbach, Klaus; Dapunt, O.; Karck, Matthias (The thoracic and cardiovascular surgeon, 2010)
A German registry for acute aortic dissection type A (GERAADA) was initiated by the Working Group for Aortic Surgery and Interventional Vascular Surgery of the German Society for Thoracic and Cardiovascular Surgery (GSTCVS) in July 2006. This web-based database was developed to record the data of patients who had undergone surgery for aortic dissection type A. From analyzing the data, we aim to learn how to improve surgical treatment and to identify parameters affecting patient outcome...